The Correlation Analysis between Corneal Biomechanical Properties and the Surgically Induced Corneal High-Order Aberrations after Small Incision Lenticule Extraction and Femtosecond Laser In Situ Keratomileusis - Wenjing Wu; Yan Wang (Journal of Ophthalmology)
Background. To investigate the correlation between corneal biomechanics and the surgically induced corneal high-order aberrations (HOAs) after small incision lenticule extraction (SMILE) and femtosecond laser in situ keratomileusis (FS-LASIK). Methods. A total of 150 right myopic eyes that underwent SMILE or FS-LASIK surgery were included in this retrospective study, 75 eyes in each group. The corneal hysteresis (CH) and the corneal resistance factor (CRF) with the corneal HOAs of the anterior, posterior, and total cornea were assessed preoperatively and three months postoperatively. Multivariate linear regression was applied to determine the correlations. Results. The preoperative CRF was significantly correlated with the induced 3rd–6th-order HOAs and spherical aberration of the anterior surface and the total cornea after SMILE and FS-LASIK surgeries (P<0.05), postoperatively. The CRF was significantly correlated with the induced vertical coma of the anterior and posterior surfaces and the total cornea after SMILE surgery (P<0.05). There was a significant correlation between the CRF and the induced posterior corneal horizontal coma after FS-LASIK surgery (P=0.013). Conclusions. The corneal biomechanics affect the surgically induced corneal HOAs after SMILE and FS-LASIK surgery, which may be meaningful for screening the patients preoperatively and optimizing the visual qualities postoperatively.